Letters - Sacks, Oliver, 1933-2015 (Alfred A. Knopf, 2024)
"The letters of one of the greatest observers of the human species, revealing his intimate thoughts on life and work, friendship and art, medicine and society, and the richness of his relationships with friends, family and scientists over the decades A prolific correspondent, Dr. Oliver Sacks--who describes himself variously in these pages as "a philosophical physician," "an astronomer of the inward," a "neuropathological Talmudist," and "a consummate observer" with "a pure love for phenomena"--wrote letters throughout his life to his parents, his beloved Aunt Lennie, to friends and colleagues from London, Oxford, California, and around the world. The pages begin with his arrival in America as a young man, eager to establish himself away from the confines of postwar England, and carry us through his bumpy early career in medicine and the discovery of his writer's voice and métier; his weightlifting, motorcycle-riding years and his explosive seasons of discovery with the patients who populate his book Awakenings; his growing interest in matters of sight and the musical brain; his many friendships and exchanges with fellow writers, artists and scientists (to say nothing of astronauts, botanists, and mathematicians), and his deep gratitude for all these relationships at the end of his life. From Francis Crick and Jane Goodall to W. H. Auden and Susan Sontag, from lovers to patients, and ordinary folk who wrote to him with their odd symptoms and questions, all are treated equally to Sacks's lyrical, ferocious, penetrating and at times hilarious observations. His musings often contain the first detailed sketches of an essay forming in his mind. Sensitively introduced and edited by Kate Edgar, Sacks's longtime assistant (and one of his correspondents), the letters deliver a complete portrait of Sacks as he wrestles with the workings of the brain and mind. We see, through his eyes, the beginnings of modern neuroscience as it unlocks many secrets of how the human brain defines us. We experience the arc of a remarkable personal evolution, closely following the thought processes of one of the twentieth century's great intellectuals, whose life was long and productive and whose words, as evidenced in these pages, were unfailingly shaped with generosity and wonder toward other people."--